Anti-Chattering Strategy using Twisting Controller. Issue 13 (2018) - Martínez-Fuentes, C. Arturo; Moreno, Jaime A.; Fridman, Leonid
Abstract: In this paper a disturbed first order system with unknown control coefficient is stabilized globally and in finite time by means of a linear PI controller and the integral of the Twisting controller allowing the rejection of the uncertainties and disturbances despite of the unknown control coefficient. The stability of the proposed control law is proved by a Lipschitz continuous Lyapunov function. In simulations section the performance of proposed controller and generalized super-twisting algorithm in the presence of the bounded measurable noises is discussed.